Seasonal changes and determination of heavy metal concentrations in Veshaw river of the Indian western Himalaya - Rather, Rauoof Ahmad; Ara, Shoukat; Sharma, Sanjeev; Padder, Shahid Ahmad; Lone, Farooq Ahmad; Mir, Shakeel Ahmad; Baba, Zahoor Ahmad; Ayoub, Iqra Binti; Mir, Ikhlaq Ahmad; Bhat, Tariq Ahmad; Baba, Tawseef Rehman (Frontiers in Environmental Chemistry, 2022)
Trace elements are ubiquitous in the environment and have been recognized as one of the vital pollutants to river system. The river Veshaw is the main water resource of the Kashmir valley and is associated with Kashmiri civilization. The Veshaw is greatly utilized for its water and food such as fish. Since it passes through many rural and urban settlements, the river gets polluted with sewage from settlements, agricultural runoff and effluent discharges from various industrial units. The effluent that finds its way into the river contains various types of pollutants including trace elements that get accumulated in reverie ecosystem including flora and fauna. Trace element levels in water and sediment were found to follow the trend as: Sangam> Khudwani > Kulgam > Nihama >Aharbal > Kingwattan. The dominance pattern of heavy metals in water was Pb > As > Cd. The overall trend showed downward increase of heavy metals indicating the effect of land area drainage and anthropogenic activities on the stream water. The dominance pattern of heavy metals in water was Pb > As > Cd. Heavy metals were significantly not traced in the middle and upstream sites. The overall trend showed downward increase of heavy metals with highest average values 0.0091 mgL-1 observed at Downstream (Sangam) during indicating the effect of land area drainage and anthropogenic activities on the stream water.